Ultrastructural Study of Cryptococcus neoformans Surface During Budding Events - Araújo, Glauber R. de S.; Alcantara, Carolina de L.; Rodrigues, Noêmia; de Souza, Wanderley; Pontes, Bruno; Frases, Susana (Frontiers in Microbiology, 2021)
Cryptococcus neoformans is a fungal pathogen that causes life-threatening infections in immunocompromised individuals. It is surrounded by three concentric structures that separate the cell from the extracellular space: the plasma membrane, the cell wall and the polysaccharide capsule. Although several studies have revealed the chemical composition of these structures, little is known about their ultrastructural organization and remodeling during C. neoformans budding events. Here, by combining the latest and most accurate light and electron microscopy techniques, we describe the morphological remodeling that occurs among the capsule, cell wall and plasma membrane during budding in C. neoformans. Our results show that the cell wall deforms to generate a specialized region at one of the cell’s poles. This region subsequently begins to break into layers that are slightly separated from each other and with thick tips. We also observe a reorganization of the capsular polysaccharide around the specialized regions. While daughter cells present their polysaccharide fibers aligned in the direction of budding, mother cells show a similar pattern but in the opposite direction. Also, daughter cells form multilamellar membrane structures covering the continuous opening between both cells. Together, our findings provide compelling ultrastructural evidence for C. neoformans surface remodeling during budding, which may have important implications for future studies exploring these remodeled specialized regions as drug-targets against cryptococcosis.